Prediction of nitrogen behaviour in the AOD process by a time-dependent thermodynamic model. (2nd January 2022) - Wei, Wenjing; Gustavsson, Joel; Samuelsson, Peter B.; Gyllenram, Rutger; Tilliander, Anders; Jönsson, Pär G.
ABSTRACT: In this work, a time-dependent thermodynamic AOD process model, TimeAOD3™, is proposed to be used as a prediction model at practice to reach the desired nitrogen level to lower the cost and carbon footprint. The model is developed from an existing model and integrated with Thermo-Calc®. The modelling results suggest a fairly good prediction when compared with production-scale heats. The relative error of dissolved nitrogen content during and after decarburisation is −0.05 < RE < 1.36 and −0.23 < RE < 0.29, respectively. Besides, most modelled dissolved N% are higher than the measurement during decarburisation. This is probably owing to the formation of high turbulence flow and CO gas bubble which can flush the dissolved nitrogen out of the bath at practice. Moreover, dissolved C%, Cr% in bath and Cr2 O3 %, CaO%, MgO% in slag, as well as bath temperature are also compared and studied.